Evaluating Capacity Limits for Worst Case of Transceiver Impairments for Massive MIMO Systems under Optimum Power Allocation - Amjad Quazi, Dr. Sanjeev Kumar Gupta, Sumaiya Mateen, Dr. Paresh Rawat (International Journal of Control and Automation, 2020)
Increasing spectral efficiency and capacity of broadband communication use of massive antenna structures have become popular recently. The performance of the Massive MIMO system transceivers must improve under the presence of the hardware impairments. The performance degraded significantly with increasing massive MIM O dimensions. The Massive MIMO transceivers works over wide range of SNR also increases with gigantic MIMO dimensions. The huge Massive MIMO size limits to use low cost hardwires casing impairments and limits the capacity range. The multipath channel offers the more multiplexing gain. Therefore this paper proposes to evaluate the capacity limits over the Massive MIMO system with16x16 and 64 x 64 structures In order to evaluate the performance the system is modelled with Rayleigh fading the worst case of hardware impairments of Kapppa=0.15 for the cellular network..The next generations huge massive MIMO system provides enhanced multiplexing gain and but also limits capacity under impairments. Paper evaluates the 5G Massive MIMO capacity limits using water filling power optimization algorithms and capacity limits are mathematically represented. It is found that the performance is degrades under worst case of impairment. And even using optimization does not limits capacity sor serious attentions are require to give to improve performance.